Parent Gender Affects the Influence of Parent Emotional Eating and Feeding Practices on Child Emotional Eating - Trevino, Shaina D.; Kelly, Nichole R.; Budd, Elizabeth L.; Giuliani, Nicole R. (Frontiers in Psychology, 2021)
Extant research supports a direct association between parent’s own emotional eating and their child’s emotional eating, and demonstrates correlations among parent emotional eating, feeding practices, and child emotional eating. However, the majority of this work focuses on the separate influences of these factors. The current study aims to add to the literature by simultaneously examining the indirect effects of three major parental feeding practices (i.e., emotion regulation, instrumental, and restrictive feeding) in the association between parent emotional eating and child emotional eating, and exploring how these indirect effects vary based on parent gender. Parents (86 fathers, 324 mothers) of an elementary school-age child (M = 8.35, SD = 2.29, range = 5-13) completed an online survey through Qualtrics Panels. Results suggested that restrictive feeding partially accounted for the association between parent and child emotional eating in the combined sample of mothers and fathers. Exploratory analyses revealed that the indirect effects of parental feeding practices in the association between parent emotional eating and child emotional eating varied based on parent gender. Among mothers, restrictive feeding was the only feeding practice that partially accounted for the association between maternal and child emotional eating, whereas all three feeding practices fully accounted for the association between father and child emotional eating. As the bulk of the literature on parent emotional eating and feeding has solely focused on mothers, these findings offer insight into how feeding practices may differentially function in the relation between parent emotional eating and child emotional eating for mothers versus fathers.